Low-Velocity Impact Response Of Thermoplastic Honeycomb Core Sandwich Structure With Aluminium Face Sheet - Sawal, Nurashikin (2011)
The low-velocity impact response of thermoplastic honeycomb core sandwich structure with aluminium face sheet was investigated by conducting a series of drop-weight impact tests on a range of temperatures and thickness considered. By using an instrumented drop-weight impact tower, the impact energy were varied according to variation of drop heights. In this study, a simple energy-balance model was used to predict the impact response of the sandwich structure which accounts for energy absorption in bending, shear and contact deformations. For each test, the resulting impact force was used as an indicator to determine the impact response of the sandwich structure which the value obtained from the experiment were compared to those calculated from the model. The maximum impact force for a given impact energy was found to be increase with core and face sheet thickness but decreases with increasing temperature.Mechanical tests such as flexural and compression tests were also conducted in this study in order to determine the flexural and compression properties of the sandwich structure. The results found that both flexural modulus and strength were rate-insensitive over the range of crosshead displacement rate. By using the energy-balance model, the agreement between the experimental value and theoretical value was found to be good with a small scatter of data in the maximum impact force values. Damage and failure modes from the test were observed by using naked eye and optical microscope in order to determine the types of damage occured and the impact damage area of the structure.